Eddie Martinez - Sculptures - Price, Matt
As with his paintings, the sculptures of Eddie Martinez are dynamic, colourful and bold explorations of abstract shape, line and form. In this, the first comprehensive survey of the artist?s sculptural works to date, the eclectic range of materials he employs comes to the fore, with lo-fi and found materials such as plaster, cardboard, wood, plastic and rubber (not to mention lobster traps, buoys and badminton rackets) reaching their apotheosis in exquisitely cast bronzes. Playful, energetic and exuberant, they are simultaneously filled with an equal sense of melancholy, nostalgia and humility. With a distinctive formal and aesthetic unity across his sculptural practice, the works offer an elegiac exposé of physical matter, consumption, entropy and decay today, highlighting myriad raw materials, industrial and artisanal production and manufacturing processes, and their resultant surfaces, textures and other qualities both when new and as they age and degrade. 00Exhibition: Frieze London, United Kingdom (06.10.-09.10.2016)
Keywords: Martinez, Eddie -- 1977-; Malerei; Plastik; Ausstellungskatalog -- Timothy Taylor Gallery -- London; Werkverzeichnis